Prognostic significance of cribriform adenocarcinoma of the lung: validation analysis of 1,057 Japanese patients with resected lung adenocarcinoma and a review of the literature - Nakajima, Naoki; Yoshizawa, Akihiko; Rokutan-Kurata, Mariyo; Noguchi, Misa; Teramoto, Yuki; Sumiyoshi, Shinji; Kondo, Kyoko; Sonobe, Makoto; Hamaji, Masatsugu; Menju, Toshi; Date, Hiroshi; Haga, Hironori (Translational lung cancer research, 2021)
Cribriform-predominant adenocarcinoma of the lung (Cribri-ADC) is a recently described tumor growth pattern. However, its prognostic impact has not been clearly determined. We analyzed the data of a series of 1,057 Japanese patients with resected lung adenocarcinoma to identify the clinical significance of Cribri-ADC. Cribriform pattern (Cribri-p) is defined as invasive back-to-back fused tumor glands with poorly formed glandular spaces or invasive tumor nests comprising tumors cells that produced glandular lumina. We investigated the correlations of Cribri-p and Cribri-ADC with clinicopathological factors as well as disease-free survival (DFS) and overall survival (OS). Cribri-p was present in 217 patients (20.5%) and Cribri-ADC was determined in 25 patients (2.4%). Cribri-p was associated with larger tumor size, pleural invasion, vascular invasion, lymphatic invasion, and spreading through air spaces (STAS) (all, P<0.0001). Cribri-ADC was associated with younger age (P=0.019), vascular invasion (P=0.0025), STAS (P<0.0001), and rearrangement (P=0.012). The DFS curve of patients with Cribri-ADC was identical to that of patients with solid adenocarcinoma; however, the OS curve was located between that of patients with papillary and acinar adenocarcinoma. Of the 10 patients who had tumor recurrences, eight had mutations or rearrangement, six of whom achieved relatively long survival (median, 64.6, range, 37.4-113 months) following treatment with tyrosine kinase inhibitors (TKIs). In multivariate analysis, Cribri-ADC was not an independent prognostic factor of either recurrence or death. Cribri-ADC is associated with a higher risk of recurrence; however, most patients can be successfully treated with TKIs.